FAKTOR-FAKTOR YANG MEMENGARUHI FIRM PERFORMANCE PADA PERUSAHAAN MANUFAKTUR DI BEI - Syane Anggita Santoso; viriany viriany (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this study is to analyze the influence of Liquidity, Capital Structure, Company’s Growth and Firm Size on Firm Performance on manufacturing company listed on the Indonesia Stock Exchange from 2017-2019. Sample was selected using purposive sampling method and the valid data was 36 companies. Data processing techniques using multiple regression analysis what helped by Eviews 11.0 for windows and Microsoft Excel 2013. The results of this study show that Capital Structure has a negative and significant effect on the Firm Performance while Liquidity, Company’s Growth and Firm Size have no significant effect on the Firm Performance. The implication of this research is the need to increase management focus to increase Firm Performance which will provide good signals for investors.